Evaluating impacts of OmniGen-AF on feed intake, milk yield, and milk composition of dairy cows during the transition to lactation - Newton, Shane P.; Takiya, Caio; Bradford, Barry; Mendonca, Luis; Hulbert, Lindsey E.; McGill, Jodi (My University, 2018)
When dairy cows go through parturition, their immune system is the most suppressed it will be in their life. Omnigen (Phibro Animal Health, Teaneck, NJ) is a feed additive product that is promoted as giving better immune responses to dairy cattle during the transition from pregnancy to full milk production. This study is being conducted to evaluate the effects of adding this product to the total mixed ration (TMR), specifically on feed intake, milk yield, and milk composition. Past studies have shown increases in feed intake, and milk yield. Thirty pre-partum cows were assigned to a completely randomized block design based on parity and expected calving date. Then, they were randomly assigned to either a control treatment, or OmniGen-AF (56 g/hd/day) mixed into the top third of the TMR and distributed evenly across feedings. The cows received these treatments from 60 d prior to expected calving date through 49 d post calving. Dry cows were allotted access to the designed treatment rations through an electronic gated feeding system, with one cow assigned per gate. Post calving, the cows were moved to a tie-stall barn with individual feed bunks suspended from load cells, monitored continuously by a computer. Cows were fed twice daily and milked three times daily. Milk samples were collected at each milking on 3 days each week (from week 1 to 7 of lactation) and were analyzed for concentrations of fat, true protein, lactose, and somatic cells by Heart of America DHIA. Data were analyzed using mixed models to account for treatment, parity, time, and their interactions, and significance was declared at P<0.05. When looking at data gathered from the first 20 cows, no significant effects were detected for feed intake, milk yield (mean 45.6 ± 2.0 kg/d), or change in body weight over the treatment period. Milk protein was the only performance variable affected by treatment; Omnigen increased milk protein concentration relative to control (2.84 vs. 2.64 ± 0.09%, P < 0.01). In conclusion, feeding Omnigen during the transition to lactation increased milk protein concentration, but no other productivity responses were observed in this relatively small cohort.
Keywords: Spring 2018